Porous carbon for nitrogen-oxygen co-doped capacitor based on benzoxazine solid-phase conversion and preparation method and application thereof
Based on the method based on the transformation of benzene -pic -pheasine solid -phase conversion, the N, O high -doped resin of the high degree of connectivity is prepared, and the high ratio surface area and the high -electricity value of the high -power capacity are obtained by activating carbonization. The problem of low conversion rate of porous carbon materials has a low conversion rate, and it has achieved efficient preparation and high -performance applications.
Patent Information
- Application Number
- CN202411946131.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the prior art, the precursor conversion rate of porous carbon materials is low, resulting in limited efficient preparation of materials and high performance applications.
Using a method based on the transformation of benzene -picinzine solid -phase conversion, it is solidified, solid -phase conversion, activation, and carbonization by solidifying, solid -phase conversion, activation, and carbonization of benzide monopozide monopoly in the structure of neighboring. , And get a high -ratio surface area and high -power capacity N, o by activating carbonization, a co -doped porous carbon.
The overall utilization rate of the front -drive body has been improved. The porous carbon materials obtained have a high surface area and capacitance value, which is suitable for the fields of supercapacitors and batteries.
Smart Images

Figure CN119370829A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of porous carbon preparation, and specifically relates to a porous carbon for nitrogen-oxygen co-doped capacitors based on benzoxazine solid phase conversion, and a preparation method and application thereof. Background Art
[0002] Three-dimensional porous carbon materials rich in nitrogen and oxygen have huge specific surface area and high porosity. At the same time, the doping of nitrogen and oxygen atoms effectively regulates the arrangement of the electron cloud around the carbon skeleton. Therefore, this material exhibits excellent catalytic activity in a variety of electrochemical reactions. This material has extremely important application value in the fields of electrocatalytic nitrogen reduction to prepare ammonia, electrocatalytic carbon dioxide reduction, electrocatalytic water decomposition, as well as batteries and supercapacitors.
[0003] As a new type of phenolic resin, benzoxazine resin not only has excellent properties similar to traditional phenolic resins in thermal properties, mechanical properties, flame retardancy, etc., including near-zero shrinkage curing, low water absorption, good dimensional stability, excellent FST (fire, smoke, toxicity) properties, etc. Its high residual carbon rate and intrinsic high heteroatom doping make it a potential excellent porous carbon precursor.
[0004] With the rapid development of supercapacitors, batteries and other fields, efficient research and development of energy storage carbon materials has become the direction of scientific researchers and industrial R&D personnel. Patent No. (CN117317223A) uses sodium alginate as a precursor of porous carbon, but its mass residual rate (i.e. the yield of carbon materials) is only 29.4% at most. How to develop and efficiently prepare porous materials with high specific surface area and high capacitance for capacitors is an urgent problem to be solved in the industry. Summary of the invention
[0005] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a porous carbon for nitrogen-oxygen co-doped capacitors based on benzoxazine solid phase conversion. The present invention is based on benzoxazine solid phase conversion chemistry to prepare a highly cross-linked N, O highly doped resin, and then efficiently obtains N, O co-doped porous carbon by activated carbonization. This not only broadens the preparation method of heteroatom-doped porous carbon, but also the prepared porous carbon has a high specific surface area and a high capacitance value, and effectively solves the problem of low conversion rate of precursor (benzoxazine monomer) to carbon material.
[0006] The present invention also provides a preparation method and application of the porous carbon for nitrogen-oxygen co-doped capacitors based on benzoxazine solid phase conversion.
[0007] Technical solution: In order to achieve the above-mentioned purpose, the porous carbon for capacitors using nitrogen and oxygen co-doped based on benzoxazine solid phase conversion is obtained by solidification, solid phase conversion, activation and carbonization of benzoxazine monomers containing ortho-amide structures; the structure of the benzoxazine monomers containing ortho-amide structures is as follows: , Where -R is one of the following structures: .
[0008] The method for preparing porous carbon for capacitors using nitrogen and oxygen co-doped based on benzoxazine solid phase conversion of the present invention comprises the following steps: (1) mixing an acyl chloride compound and o-aminophenol and dissolving them in an organic solvent, heating them for reaction, and evaporating the organic solvent after stopping the reaction to obtain an o-aminophenol compound; (2) dissolving an ortho-amide phenol compound, an amine compound and polyformaldehyde in an organic solvent, heating for reaction, stopping the reaction, and then recrystallizing to obtain a benzoxazine monomer containing an ortho-amide structure; (3) The benzoxazine monomer containing an ortho-amide structure is cured and solid-phase converted to obtain a resin precursor, and the resin is activated and carbonized to obtain porous carbon for capacitors based on benzoxazine solid-phase conversion of nitrogen and oxygen.
[0009] Wherein, the acyl chloride compound described in step (1) is any one of the following:
[0010] Wherein, in step (1), the molar ratio of the acyl chloride compound to o-aminophenol is 1:1-1:1.1.
[0011] Preferably, in step (1), the molar ratio of the acyl chloride group in the acyl chloride compound to the amino group in o-aminophenol is 1:1.
[0012] Wherein, the heating temperature in step (1) is 30-60° C., the reaction time is 1-4 hours, and the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
[0013] Wherein, the amine compound in step (2) is diaminodiphenylmethane, and the molar ratio of the ortho-amidephenol compound, diaminodiphenylmethane and polyformaldehyde is 2:1:4-2:1:4.8.
[0014] Among them, diaminodiphenylmethane, its molecular formula is as follows: .
[0015] Wherein, in step (2), the heating temperature is 80-120° C., the reaction time is 6-10 hours, and the organic solvent is one or more of toluene, xylene, dioxane and N,N-dimethylformamide.
[0016] The solidification and solid phase conversion in step (3) is to react the benzoxazine monomer containing the ortho-amide structure at 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C and 260°C for 1-3 hours respectively.
[0017] The activation process in step (3) is to mix the product after solid phase conversion with potassium hydroxide, ammonium persulfate or potassium ferrate in a mass ratio of 1:1-1:3.
[0018] The carbonization process in step (3) is to carbonize the activated sample at a high temperature of 600-900° C. for 1-3 h in an inert atmosphere.
[0019] The invention discloses an application of the porous carbon for capacitors co-doped with nitrogen and oxygen based on solid phase conversion of benzoxazine in supercapacitors and batteries.
[0020] The present invention utilizes ortho-amide type phenolic compounds, amine compounds, and polyformaldehyde, which are dissolved in a solvent, reacted at 80-120° C. for 6-10 hours, and the reaction liquid is rotary evaporated after stopping the reaction, and the obtained benzoxazine is subjected to high-temperature solid phase conversion to obtain a resin precursor, and then the precursor and the activator are mixed and carbonized at high temperature to obtain porous carbon for nitrogen-oxygen co-doped capacitors based on benzoxazine solid phase conversion. The advantages of the present invention are: ① The N, O highly doped resin prepared by the benzoxazine solid phase conversion method can effectively retain the defect structure during the carbonization process due to its high crosslinking density, and realize the efficient utilization of carbon. ② The obtained N, O co-doped porous carbon has a higher capacitance value due to its more defective structures and larger specific surface area. ③ The synthesis process is relatively simple, with low equipment requirements, high yield, low energy consumption, and is suitable for large-scale production.
[0021] The present invention uses the benzoxazine solid phase conversion method for the first time to prepare a benzoxazolyl-based high-crosslinked resin porous carbon precursor, which improves the problem of inefficient utilization of precursors in the traditional process of preparing porous carbon. The overall utilization rate of the precursor exceeds 45%. The obtained porous carbon not only retains more defective structures, but also obtains a larger specific surface area, which can effectively improve its capacitance value as a capacitor material.
[0022] The present invention adopts a special structural monomer and prepares a N, O highly doped resin by a solid phase conversion method. Due to its high crosslinking density, it can effectively retain the defect structure during the carbonization process and realize efficient utilization of carbon. Secondly, the obtained N, O co-doped porous carbon has a higher capacitance value due to its more defect structures and larger specific surface area.
[0023] The present invention synthesizes a new precursor structure and achieves high utilization and high performance of the precursor through a specific method. The present invention realizes efficient utilization of carbon (>50%) for the first time through a benzoxazine solid phase conversion method while having a high capacitance value, ensuring a high conversion rate of the precursor to carbon material. The present invention utilizes a specific monomer structure and its structural and solid phase conversion characteristics to obtain carbon materials through high conversion rates while obtaining excellent performance. The present invention uses a specific benzoxazine monomer structure, and its high cross-linking density and aromatic ring content result in less volatilization loss during the firing process, thereby obtaining a higher yield.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following advantages: 1. The N, O highly doped resin prepared by the benzoxazine solid phase conversion method of the present invention can effectively retain the defect structure during the carbonization process and achieve efficient utilization of carbon due to its high crosslinking density.
[0025] 2. The N, O co-doped porous carbon prepared by the present invention has a higher capacitance value due to its more defective structures and larger specific surface area.
[0026] 3. The synthesis process is relatively simple, with low equipment requirements, high yield, low energy consumption, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the infrared spectrum of the benzoxazine monomer with ortho-amide structure obtained in Example 1; Figure 2 This is the nuclear magnetic resonance spectrum of the ortho-amide benzoxazine monomer obtained in Example 1; Figure 3 Thermogravimetric spectrum of the precursor after solid phase conversion obtained in Example 1; Figure 4 This is the BET curve of N,O co-doped porous carbon obtained in Example 1; Figure 5 The charge and discharge curves of the N,O co-doped porous carbon obtained in Example 1 in the capacitor test; Figure 6 This is the CV curve of the N, O co-doped porous carbon obtained in Example 1 in the capacitor test. DETAILED DESCRIPTION
[0028] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0029] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0030] Example 1
[0031] 0.05 mol of 2-thiophenecarbonyl chloride and 0.05 mol of o-aminophenol were dissolved in 20 ml of DMF, stirred and reacted at 30°C for 4 hours, and the solvent was spin-dried to obtain the o-amide phenol compound 1. 0.0050 mol of o-amide phenol compound 1, 0.0025 mol of diaminodiphenylmethane, and 0.011 mol of polyformaldehyde were dissolved in 50 ml of toluene, stirred and reacted at 110°C for 9 hours, and a benzoxazine monomer containing an o-amide structure was obtained after recrystallization. The chemical reaction equation is as follows: .
[0032] The prepared benzoxazine monomer containing an ortho-amide structure was reacted at 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C and 260°C for 2 hours respectively to obtain a resin precursor. The obtained resin precursor was mixed with 2 times the mass of KOH and then carbonized at 800°C for 2 hours in an argon atmosphere in a tubular furnace to obtain a N, O co-doped porous carbon material for capacitors.
[0033] Figure 1 This is the infrared spectrum of the prepared benzoxazine monomer containing an ortho-amide structure; Figure 2 This is the nuclear magnetic resonance spectrum of the prepared benzoxazine monomer with ortho-amide structure. Figure 3 This is the thermogravimetric spectrum of the precursor after solid phase conversion obtained in Example 1. Figure 4 This is the BET curve of N, O co-doped porous carbon obtained in Example 1. Figure 5 This is the charge and discharge curve of the N, O co-doped porous carbon obtained in Example 1 in the capacitor test. Figure 6 This is the CV curve of the N, O co-doped porous carbon obtained in Example 1 in the capacitor test.
[0034] In this embodiment, the yield of converting the resin into carbon material by thermogravimetric curve is 50.56%, and the specific surface area of the porous carbon is 1820.9867 m² / g. When used in a capacitor, under the three-electrode test conditions, 2 mg of porous carbon material is mixed with 100 μL of 5 g / L polytetrafluoroethylene ethanol solution to form a slurry, which is evenly coated on a foam nickel electrode as a working electrode, using Ag / AgCl as a reference electrode, a Pt sheet as a counter electrode, and a 6 M KOH solution as an electrolyte. When the charge and discharge rate is 0.5 A / g, its capacitance is 441.34 F / g.
[0035] Example 2
[0036] The 2-thiophenecarbonyl chloride in Example 1 was replaced by 2-pyridinecarbonyl chloride. The other steps were the same as those in Example 1.
[0037] The specific chemical formula of the benzoxazine monomer corresponding to the ortho-amide structure obtained is: .
[0038] In this embodiment, the yield of converting the resin into carbon material is 48.52%, and the specific surface area of the porous carbon is 1631.5963 m² / g. When used in a capacitor, under the three-electrode method test conditions, when the charge and discharge rate is 0.5 A / g, its capacitance is 392.82 F / g.
[0039] Example 3
[0040] The 2-thiophenecarbonyl chloride in Example 1 was replaced by furancarbonyl chloride. The other steps were the same as those in Example 1.
[0041] The specific chemical formula of the benzoxazine monomer corresponding to the ortho-amide structure obtained is: .
[0042] In this embodiment, the yield of converting the resin into carbon material is 47.92%, and the specific surface area of the porous carbon is 1523.4153 m² / g. When used in a capacitor, under the three-electrode method test conditions, when the charge and discharge rate is 0.5 A / g, its capacitance is 382.12 F / g.
[0043] Comparative Example 1
[0044] In this comparative example, the method of Example 1 is adopted, and the obtained resin precursor is not mixed with KOH. In this comparative example, the yield of converting the resin into carbon material is 50.42%, and the specific surface area of the porous carbon is 12.7821 m² / g. When it is used in a capacitor, under the three-electrode method test conditions, when the charge and discharge rate is 0.5A / g, its capacitance is 6.13F / g. In this comparative example, due to the absence of the activator KOH, pores cannot be formed, and the specific surface area drops sharply, resulting in almost no performance.
Claims
1. A porous carbon for capacitors co-doped with nitrogen and oxygen based on benzoxazine solid phase conversion, characterized in that: The benzoxazine monomer containing an ortho-amide structure is obtained by solidification, solid phase conversion, activation and carbonization; the structure of the benzoxazine monomer containing an ortho-amide structure is as follows: , Where -R is one of the following structures: 。 2. A method for preparing porous carbon for capacitors using nitrogen and oxygen co-doped based on benzoxazine solid phase conversion according to claim 1, characterized in that: The steps include: (1) mixing an acyl chloride compound and o-aminophenol and dissolving them in an organic solvent, heating them for reaction, and evaporating the organic solvent after stopping the reaction to obtain an o-aminophenol compound; (2) dissolving an ortho-amide phenol compound, an amine compound and polyformaldehyde in an organic solvent, heating for reaction, stopping the reaction, and then recrystallizing to obtain a benzoxazine monomer containing an ortho-amide structure; (3) The benzoxazine monomer containing an ortho-amide structure is cured and solid-phase converted to obtain a resin precursor, and the resin is activated and carbonized to obtain porous carbon for capacitors based on benzoxazine solid-phase conversion of nitrogen and oxygen.
3. The preparation method according to claim 2, characterized in that: The acyl chloride compound described in step (1) is any one of the following: 。 4. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of the acyl chloride compound to o-aminophenol is 1:1-1:1.
1.
5. The preparation method according to claim 2, characterized in that: In step (1), the heating temperature is 30-60° C., the reaction time is 1-4 hours, and the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
6. The preparation method according to claim 2, characterized in that: In step (2), the amine compound is diaminodiphenylmethane, and the molar ratio of the ortho-amidephenol compound, diaminodiphenylmethane and polyformaldehyde is 2:1:4-2:1:4.
8.
7. The preparation method according to claim 2, characterized in that: In step (2), the heating temperature is 80-120° C., the reaction time is 6-10 hours, and the organic solvent is one or more of toluene, xylene, dioxane and N,N-dimethylformamide.
8. The preparation method according to claim 2, characterized in that: The solidification and solid phase conversion in step (3) is to react the benzoxazine monomer containing the ortho-amide structure at 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C and 260°C for 1-3 hours respectively.
9. The preparation method according to claim 2, characterized in that: The activation process described in step (3) is to mix the resin precursor after solid phase conversion with potassium hydroxide, ammonium persulfate or potassium ferrate in a mass ratio of 1:1-1:3; the carbonization process described in step (3) is to carbonize the activated sample at a high temperature of 600-900°C for 1-3h under an inert atmosphere.
10. Use of the nitrogen-oxygen co-doped porous carbon for capacitors based on benzoxazine solid phase conversion according to claim 1 in supercapacitors and batteries.
Citation Information
Patent Citations
Preparation method and application of active porous carbon
CN117317223A
Preparation method for benzoxazine resin nano-polymer sphere and benzoxazine resin nano-polymer carbon sphere
CN102225996A
Three-dimensional carbon fiber based aerogel material and preparation method thereof
CN103265010A
Main chain type benzoxazine with amide structure and preparation method of main chain type benzoxazine
CN107915817A
Preparation method of nitrogen-oxygen co-doped porous carbon materials based on bio-based benzoxazine
CN108640113A